A quintessential syndrome with a rare marvelling aetiology: Rosai-Dorfman disease presenting as Conus-Cauda syndrome. (17th February 2018) - Chhabria, Bharath A; Nampoothiri, Ram V; Nambiyar, Kaniyappan; Lad, Deepesh
Abstract : A 19-year-old woman presented with a history of severe lower backache and asymmetric proximal lower limb weakness during the past 3 months. In addition, she also suffered from lower motor neuron-type bladder and bowel symptoms. On examination, paraparesis was noted. Further, sensory examination suggested patchy asymmetric sensory loss in both lower limbs with saddle anaesthesia and areflexia. A clinical diagnosis of Conus-Cauda syndrome was made and contrast-enhanced MRI of the lumbar and sacral spine was done, which confirmed the presence of a mass lesion within the spinal canal involving the cauda equina extending up to the sacral level. She underwent partial resection of the lesion following which the neurological deficits and lower backache resolved. Histopathological evaluation and immunohistochemical analyses uncovered Rosai-Dorfman disease. There was no evidence of disease elsewhere in the body. Since the patient improved significantly following surgery and exhibited no further neurological worsening, she remains under close follow-up.